The role of tRNA-derived fragments in prostate cancer: a review: Role of tRNA-derived fragments in prostate cancer - Babaei , Shakur; Khorrami, Mehdi; Eskandari, Amirhossein; Ramazani, Masoomeh; Saffar Moghadam, Ali Akbar; Rezaei-Taviran, Mostafa; Soleimani, Shahrzad; Ghadyani, Fatemeh; Sepehr Kahrizi,; Movafagh, Abolfazl (Cellular and Molecular Biology, 2025)
Prostate Cancer (PCa) is a leading malignancy in men in developed countries. The lack of reliable prognostic markers in PCa hinders effective treatment, leading to potential patient misclassification and overtreatment with associated side effects. Recent advances in high-throughput sequencing have enabled the identification of tRNA-derived fragments (tRFs), small non-coding RNAs derived from tRNA cleavage. tRFs regulate crucial cellular processes like viability, differentiation, and homeostasis, implicating them in disease development, particularly cancer. Their potential as biomarkers for early diagnosis and prognosis, as well as targets for precision therapies, is increasingly recognized. This review focuses on the key biological functions of tRFs, including RNA silencing, translation regulation, and epigenetic regulation. It summarizes recent findings on tRFs in PCa, exploring their potential as clinical biomarkers and therapeutic targets.